A Corpus-Based Study of Writer Identities in Biology Research Articles: Clusivity and Authorial Self - Luthfia Rozanatunnisa; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2022)
An academic writing, especially a research article, is commonly, but vaguely considered that it has to be impersonal. In other words, there is a common discouragement to express writer identities in academic writings. Yet, it is recently discovered that personal attribution has such a significant role to display the interaction both between the authors and the readers and the authors and other researchers in the field. In this paper, I investigate the linguistic forms used to indicate writer identity in a number of selected research articles, and how they are used in terms of their clusivity as well as authorial self these linguistic forms construct. The data were taken from two reputable international journals: 10 research articles taken from Genome Biology, and the other 10 were taken from Molecular Systems Biology. These data were analyzed with the help of Wordsmith 5.0 (Scott 2008), an offline application which allows us to discover the occurrences of authorial references used in research articles and make concordances. A qualitative analysis was also conducted to examine the clusivity and the authorial self each linguistic form expresses. Classification on authorial selves was based on a taxonomy proposed by Tang & John (1999). The findings of this research are then aimed at indicating a tendency of writers in attributing themselves in academic writing, especially in biology research articles, where authors show more authority in their writing with the use of frequent authorial references expressing themselves as the recounters of the research process.